Removal of nutrients and heavy metals from domestic and industry using botryococcus sp. - Ab. Razak, Abdul Rafiq (2017)
Microphytes or microalgae are the most basic food source of many types of organisms on earth and blooms during the presence of dissolved inorganic phosphorus. Wastewater is a body of water that is dangerous to organic life forms when consumed or used. It contains many pollutants that can cause health problems and also affect the ecosystem of an environment. This study aims to improve the water quality of wastewaters using phycoremediation process. The objectives of this study are to determine the growth of Botryococcus sp. in different types of wastewater in terms of resistance and survival of Botryococcus sp. in phycoremediation performance, to measure the environmental factor effecting the growth of Botryococcus sp. of phycoremediation process, to optimize the physiochemical and heavy metal removal in different types of wastewaters and to evaluate the effectiveness of Botryococcus sp. to remove the pollutants in wastewaters. Phycoremediation or bioremediation process is using macroalgae or microalgae for removing pollutants, nutrients, xenobiotics and heavy metals from wastewater. This research was done by collecting microalgae sample, isolating and culturing the required Botryococcus sp. Growth optimization and followed by phycoremediation process is done to remove unwanted elements from wastewaters. The optimum growth rate of algae is achieved when salinity is at 0M, temperature at 330C, photoperiod at 12:12 and light intensity of 18000 Lux. Result shows that the highest nitrate removal percentage occurs in semiconductor (100%), followed by palm oil mill effluent (97.29%), textile wastewater (98.04%) and domestic wastewater (85.43%). Total Phosphorus removal indicates the highest percentage for domestic wastewater (100%), palm oil effluent (99.2%), textile wastewater (98.44%) and semiconductor (50.39%). From this research, it is found that the best overall removal of physiochemical and heavy metal content occurs in palm oil mill effluent followed by domestic wastewater, semiconductor wastewater and textile wastewater.